Advances in drug delivery systems for the management of gout and hyperuricemia - Peng, Zining; Meng, Fanyu; Deng, Qian; Huang, Yuanbo; Mao, Danning; Long, Yuan; Yan, Weitian; Peng, Jiangyun; Wang, Xingqiang; Liu, Nian (Frontiers in Pharmacology, 2025)
Gout and hyperuricemia represent significant global health burdens, characterized by painful inflammatory arthritis and systemic metabolic dysfunction, respectively. Current pharmacological management faces substantial limitations, including poor bioavailability, systemic toxicity, narrow therapeutic indices, immunogenicity, and suboptimal patient adherence due to frequent dosing and adverse effects. These challenges underscore the critical need for innovative therapeutic strategies. Advanced drug delivery systems (DDSs) have emerged as transformative solutions to overcome these hurdles. This comprehensive review critically analyzes recent advances in DDSs tailored to the management of gout and hyperuricemia. We first elucidate the intricate pathophysiological mechanisms linking hyperuricemia, monosodium urate (MSU) crystal deposition, NLRP3 inflammasome activation, and chronic inflammation. We then systematically explore cutting-edge DDS platforms, including lipid-based, polymer-based, and other systems. These engineered drug delivery systems significantly enhance therapeutic outcomes in gout and hyperuricemia by improving drug solubility, enabling targeted delivery, providing sustained release, facilitating synergistic drug co-delivery, and responding to pathological microenvironments, although preclinical evidence is limited and clinical evidence supporting their efficacy and safety remains sparse. Finally, we highlight translational challenges and future directions while emphasizing the considerable promise of integrating AI, biomaterial science, and personalized medicine to advance patient-centric DDS. Although progress has been made, sustained interdisciplinary collaboration and rigorous clinical validation remain critical to translate these innovations into tangible improvements in long-term disease management and quality of life for patients with gout and hyperuricemia.